Um estudo do gênero discursivo comentário interpretativo-crítico a partir das redações do vestibular da Unioeste - Cardoso, Denize Juliana Reis (2022)
This study aims at analising the discursive genre Critical-Interpretive Commentary (CIC) from essays written by candidates for the entrance exam of the State University of West Paraná - UNIOESTE. CIC is one of the three genres currently required for the test; however, there are no studies on it and, hence, the need to investigate how it is evaluated by the Permanent Board of Correction. Thus, we question is: how is the discursive genre interpretive-critical commentary configured from the essays corrected by the evaluation board of Unioeste? To answer the question, we try to configure the discursive genre interpretive-critical commentary from these essays. In order to achieve the proposed objective, the research is based on the theoretical assumptions of Applied Linguistics and on the Bakhtinian concepts of utterance and discourse genre. This research is characterized by being of a social nature, with a qualitative approach supported by document analysis. Data generation is based on documents related to Unioeste entrance exams: public notices and candidate manuals, ten essays analyzed to CIC essays that obtained high marks in the 2018 and 2019’s as well as two essays that obtained low grades, from the same entrance exams. The analyzed texts were selected in order to observe what the Board of Correction, from the candidate manual, considers pertinent to CIC, in accordance with the criteria established for the correction of the writing test in the candidate's manuals. As a result of this study, we consider the importance of the dialogic movement “comprehend-criticize” as the staple element of CIC discursive genre.